Statistical Modelling in GLIM4 - Aitkin, Murray (Oxford Statistical Science Ser., 2005)
Ideal for graduates and research students in applied statistics and a wide range of quantitative disciplines, this text gives a comprehensive treatment of the theory of statistical modelling with generalised linear models with an emphasis on applications of the theory to practical problems, using the widely available package GLIM4.